'Once they pass you, They may be gone forever': Humanitarian Duties and Professional Tensions in Safeguarding and Anti-Trafficking at the Border. (7th March 2016) - Hadjimatheou, Katerina; Lynch, Jennifer K.
Abstract: Border crossings are considered sites of unique opportunity to identify and protect victims of trafficking. UK government reforms have given Border Officers new roles and responsibilities as humanitarian first responders. This paper explores how Border Officers reconcile this aspect of their work with their role as enforcers of immigration law and their increasingly militarized status as protectors of national sovereignty and security. Drawing on in-depth interviews with a specialized team of Safeguarding and Anti-trafficking (SAT) Officers at a UK airport, we identify the emergence of a distinct SAT subculture, characterized by a sense of moral purpose and moral community, and of doing difficult but meaningful and highly skilled work that others are too indifferent, feckless or intimidated by to take on.